BUSINESS TRENDS OVERVIEW: ILLUSTRATING THE FUTURE FROM THE LENS OF MOZILLA CORPORATION - Hamid, Syaiful Rizal; Chew, Boon Cheong; Halim, Sarah; Abdullah, Muhammad Azfar (Journal of Technology Management and Business, 2014)
This paper discusses how business and social trends will look like in the future. In order to do this, the researchers synthesized the results from an in-depth literature review of business trends that have been developed overtime and predict how they will be developed in the future, as we envision the future trend. By doing this, the potential impacts of sixteen main drivers are mapped onto the corresponding Mozilla’s future context, as this provides information on how the business might change in the future. With the use of systematic approach on evidence practices, this research has been able to predict the movement of future changes. In exploring ways on evidence-informed management reviews might be achieved, the researchers evaluated the process of systematic review used in the networking, in order to help open source innovators create businesses to change the world. As a result, business trends might get high impact for the best performance assessment in which it is addressed in various ways. Keywords: